1993
DOI: 10.1016/0014-5793(93)80224-i
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight aspartic endopeptidase generates a coronaro‐constrictory peptide from the β‐chain of hemoglobin

Abstract: Studying the influence of brain cathepsin D (EC 3.4.23.5) and high molecular weight (HMW) aspartic endopeptidase (EC 3.4.23.-) on the processing of hypothalamic calmodulin-binding coronaro-constrictory peptide factors from the p-chain of globin it was found that only HMW aspartic endopeptidase generates the fragment 3140 of the p-chain of bovine hemoglobin (Hb) by cleavage of the Leuso-Leu" and Phe40-Phe41 bonds. Digestion of the B-chain of globin was performed at 37°C at an enzyme/substrate ratio of 1:80 at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…Since several hemorphins have been found in rive [3,9] and characterized by their biological properties [13,17], it will be of great interest to find out all the metabolic pathways from hemoglobin to hemorphins. Moreover, Carraway et al suggested the existence of a putative endogenous processing, similar to the renin-angiotensin system, which generates neurotensin-and enkephalin-related peptides in blood circulation [27,28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since several hemorphins have been found in rive [3,9] and characterized by their biological properties [13,17], it will be of great interest to find out all the metabolic pathways from hemoglobin to hemorphins. Moreover, Carraway et al suggested the existence of a putative endogenous processing, similar to the renin-angiotensin system, which generates neurotensin-and enkephalin-related peptides in blood circulation [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…It can be noticed that the above-mentioned hemorphins, whatever their source, originated from the same region of the beta-chain of hemoglobin (residues 32-41 of human and 31-40 of bovine hemoglobins) [2,17]. These data suggested that hemoglobin could be a precursor of biologically active peptides, and that hemorphins could be generated in the organism during physiological (catabolism of red cells) or physiopathological (inflammation) hemoglobin proteolysis [2,6,17].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…85 The globin fragment has previously been isolated from different brain regions [86][87][88][89] and has been termed LVV-haemorphin-7. Furthermore, the enzymes pepsin, 90 trypsin 88 and a high molecular weight aspartic proteinase present in bovine brain, 91 are capable of cleaving the decapeptide from globin and is suggestive of processing in the central nervous system. Apart from inhibiting opioid activity, 90 our studies indicate that LVV-haemorphin-7 also inhibits neurite outgrowth from E11 chicken sympathetic neurons and stimulates DNA synthesis in neuronal cultures (unpublished observations).…”
Section: Ang IVmentioning
confidence: 99%
“…The globin fragment, termed LVVhemorphin-7(LVV-H7), was isolated from sheep brain, using an AT 4 -radioreceptor binding assay and a multistep protein purification procedure. 109 LVV-H7 has also been previously isolated from the brain of other species, [110][111][112][113] reflecting the abundance of the peptide in the central nervous system. Furthermore, the enzymes pepsin, 114 trypsin 112 and a high molecular weight aspartic proteinase present in bovine brain 111 are all capable of processing β-globin to LVV-H7.…”
mentioning
confidence: 99%